2011
DOI: 10.1097/inf.0b013e31820d7ec4
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Urinary Tract Infections Caused by Extended Spectrum β-Lactamase-producing Enterobacteriaceae in Children

Abstract: The outcome of patients with urinary tract infections caused by extended spectrum β-lactamases (ESBL)-producing bacteria (cases) was compared with that of matched controls with urinary tract infections caused by non-extended spectrum β-lactamases-producing isolates. Significantly, more case patients received inappropriate empiric therapy than controls. Nevertheless, clinical and microbiologic outcomes as well as formation of renal scars did not differ between the 2 groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 9 publications
3
38
1
3
Order By: Relevance
“…However, patients commonly improve despite reported resistance to the antibiotic that was started (37). Possible explanations are that the child had contaminated urine rather than a true UTI, the child has asymptomatic bacteruria or the bacteria were susceptible in-vivo despite in-vitro resistance.…”
Section: Management Of Positive Urine Cultures With Multi-resistant Bmentioning
confidence: 86%
“…However, patients commonly improve despite reported resistance to the antibiotic that was started (37). Possible explanations are that the child had contaminated urine rather than a true UTI, the child has asymptomatic bacteruria or the bacteria were susceptible in-vivo despite in-vitro resistance.…”
Section: Management Of Positive Urine Cultures With Multi-resistant Bmentioning
confidence: 86%
“…In a previous study, we have shown that hospitalized children with UTI caused by ESBL-producing bacteria had favorable clinical and microbiological outcomes despite inappropriate empirical therapy compared to children with UTI caused by non-ESBLproducing bacteria who were receiving appropriate therapy (27). Furthermore, two of the children with UTI caused by ESBL-producing bacteria showed clinical and microbiological responses on the 1st day of the inappropriate therapy administration (27).…”
Section: Discussionmentioning
confidence: 95%
“…They found that patients with resistant isolates had worse outcomes as defined by longer symptom duration, higher rates of reconsultation, more subsequent antibiotic usage, and higher rates of significant bacteriuria at 1 month. Although one would expect that a UTI due to an extended-spectrum ␤-lactamase (ESBL)-producing Enterobacteriaceae would result in treatment failure using noncarbapenem ␤-lactam agents, this was refuted in several studies (44)(45)(46) in which children with UTIs due to ESBL-producing strains all had favorable clinical and microbiological outcomes despite being treated with ␤-lactam agents that were categorized as resistant by in vitro AST.…”
Section: Susceptibility Testing In Pediatric Urinary Tract Infectionmentioning
confidence: 99%